Donkey Anaphora in Non-Monotonic Environments. (6th June 2022) - Denić, Milica; Sudo, Yasutada
Abstract: Donkey anaphora in quantified sentences is ambiguous between an existential and a universal reading. The extent to which different readings are accessible depends on the quantifier, but how to model this dependence is debated (Kanazawa, 1994 ; Champollion et al. 2019 ). This study advances this debate by providing novel experimental data on the interpretation of donkey anaphora in sentences with non-monotonic quantifiers exactly 3 and all but one . We establish that while the existential reading of donkey anaphora is the preferred one with both exactly 3 and all but one, the universal reading is accessed more with all but one than with exactly 3 . These results have important implications for both Kanazawa (1994) and Champollion et al. (2019) theories, as both need to be amended to fully capture the empirical picture.